Motion analysis of U11 to U16 elite English Premier League Academy players - Goto, H.; Morris, J. G.; Nevill, M. E. (Journal of Sports Sciences, 2015)
This study examined (1) the distances and speeds covered during match play for U11 to U16 English Premier League Academy players, (2) the differences in match performance between retained and released players and (3) the effect of calculating speed zones in different ways when analysing match performance. Eighty-one academy outfield players (10-16 years old), competing in 11-a-side matches, were analysed using a 1-Hz global positioning system with three speed zones (absolute, squad and individual). Pitch dimensions were 78.7 × 54.1 m (U11 and U12), 88.0 × 64.2 m (U13) and 100.8 × 68.2 m (U14-U16). Match durations were 20 min × 2 + 15 min × 2 or 25 min × 3 (U11), 25 min × 3 (U12 and U13) and 40 min × 2 (U14-U16). The matches were part of the regular series of inter-academy matches between Premier League Academies during a season. Completion of at least a half of the duration of a match in two separate matches (mean ± s = 3.1 ± 0.8 matches; range: 2-4 matches) was the criterion for inclusion in the study. Total match running distance increased with age from ~5700 (U11) to ~6700 m/h (U15) (P < 0.01). Using the absolute speed zones, it was possible to discern differences in high-intensity (>6.0 m/s) distance covered with age (U11: 29 m/h, U16: 164 m/h, P < 0.01). Using the squad speed zones, it was possible to discern differences between retained and released players in the U11/U12s (moderate-speed running) and in the U15/U16s (walking, jogging and low-speed running) (P < 0.01). Thus, total and high-intensity running distances increase with age, and walking, jogging, low-speed running and moderate-speed running distances are greater in retained than in released players and these differences are best identified through the use of absolute and squad speed zones, respectively.